2014
DOI: 10.1002/mar.20725
|View full text |Cite
|
Sign up to set email alerts
|

Can Purchase Behavior Predict Relationship Perceptions and Willingness to Donate?

Abstract: As arts organizations frequently seek purchases and donations from the same consumers, one of their challenges is identifying which consumers are likely to become donors in the future. With all of the data currently available, many organizations are looking to their databases to predict future consumer behavior. In the customer relationship management literature, models have been developed that allow organizations to use consumer purchase data to predict future purchase behavior. This goal of this research is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…However, Durango-Cohen et al ( 2013 ) notes that reliance on RFM statistics alone introduces an aggregation bias that masks the underlying motivational factors that trigger behavior. Similarly, Johnson et al ( 2014 ) conclude that donor behavior patterns, particularly regarding the intensity of the relationship between the donor and the charitable organization, were found to be ineffective predictors of the individual’s willingness to donate. In this regard, Dolnicar and Randle ( 2007 ) suggest that motivation-based data must accompany mere RFM statistics in order to better understand the nature of the homogeneity within donor segments as well as the differences between them, thereby allowing nonprofit organizations to more effectively target each donor group with customized messaging.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…However, Durango-Cohen et al ( 2013 ) notes that reliance on RFM statistics alone introduces an aggregation bias that masks the underlying motivational factors that trigger behavior. Similarly, Johnson et al ( 2014 ) conclude that donor behavior patterns, particularly regarding the intensity of the relationship between the donor and the charitable organization, were found to be ineffective predictors of the individual’s willingness to donate. In this regard, Dolnicar and Randle ( 2007 ) suggest that motivation-based data must accompany mere RFM statistics in order to better understand the nature of the homogeneity within donor segments as well as the differences between them, thereby allowing nonprofit organizations to more effectively target each donor group with customized messaging.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, contrasting findings regarding the impact of age and gender have also been revealed by other research. For example, Johnson et al ( 2014 ) in a study conducted in a southeastern U.S. city, found no difference in gender or age regarding respondents’ willingness to donate to a performing arts organization. Similarly, Heiser ( 2006 ) reported mixed support for a significant relationship between gender differences and charitable-giving behavior.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, charities have focused on the retention of donors ( Johnson et al, 2014 ; Merchant et al, 2010 ). Previous studies have shown that communications and interactions can influence donors’ subsequent donation desires ( Gundlach et al, 1995 ; Mathur, 1996 ; Bennett, 2009 ).…”
Section: Introductionmentioning
confidence: 99%